Philosophic historiography in the eighteenth century in Britain and France - Brereton, M (2007)
The subject of this thesis is the by now traditional grouping of certain innovative works of historiography produced in eighteenth-century Britain and France; namely the historical works of Voltaire, and the historical writings of the philosophes; and, in Britain, the histories of Hume, Robertson, and Gibbon. This thesis gives a historical and expository analysis of the individual strategies of literary self-fashioning and generic appropriation which underlie this impression of resemblance. It particularly demonstrates that the major characteristics of the contemporary vision of philosophic historiography – the idea of a European history of manners or l’esprit humain, and the insistence on the rejection of the practices of the érudits – which have become incorporated within scholarly definitions of ‘Enlightenment historiography’, are well-established generic tropes, adapted and affected in France as in Britain, by authors of diverse ambitions. The invitation to assume inauthentic connections contained within the practice of philosophic historiography is shown to be embraced by Gibbon, in a notable literary challenge to the paradigms of intellectual history. This study contrasts the textual evidence of these authors’ experience of literary, personal, and political challenges regarding the definition of their role as public, intellectual writers, to the acquired image of an ideal of ‘Enlightenment writing’. It considers the Frenchness of philosophie, and the potential Britishness of Hume, Robertson, and Gibbon. As part of its wider analysis of the practice of intellectual writing with a historical focus, its scope includes the writings of British clerics and writers on religion; of French academicians; and of the late philosophe Volney, and Shelley his interpreter. The major conclusion of this thesis is that eighteenth-century British and French history writing does not support any synthesis of an Enlightenment historical philosophy, narrative, or method; while it is suggested that one of the costs of the construct of ‘Enlightenment’, has been the illusion of familiarity with eighteenth-century intellectual culture, in France as well as Britain.